Impact of perinatal oral health care education programme on the knowledge, attitude and practice behavior amongst gynaecologists of Vadodara city - Anshula Neeraj Deshpande; Steffi Jasbir Dhillon; Koodakandi Somanna Poonacha; Bhavna Harish Dave; Prriya Arun Porwal; Chirag Samuel Macwan (Wolters Kluwer Medknow Publications, 2015)
Context: Gynecologists the Primary Health Care providers, for pregnant mothers bear the unique responsibility to detect and diagnose oral health problems for timely and effective interventions. Aim: The aim of the study was to assess the impact of Perinatal Oral Health Care (POHC) education program on the knowledge, attitude and practice behavior amongst Gynaecologists of Vadodara City. Settings and Design: An analytical cross sectional study was conducted amongst Gynecologists practicing in Vadodara city, registered under Indian Medical Association (IMA), Baroda, Gujarat. Materials and Methods: A validated questionnaire survey was conducted to establish a baseline level of knowledge, attitude and practice behavior of 46 Gynecologists. After that education and awareness regarding POHC to Gynecologists was provided with the help of flip charts and resource brochures. To determine the impact of recent provision of education and awareness a post-test was conducted. Statistical analysis used: Data was analyzed by paired t-test using the SPSS Version 20. Results: The results after evaluating the data from pretest and posttest showed a mean increase of correct answers in knowledge (from 7.304-9.891; P = 0.00), Attitude (from 3.978-4.108; P = 0.49) and practice behavior (from 4.130-5.521; P = 0.00) in POHC amongst Gynecologists following the education program. Conclusions: It can be concluded that there is a need for provision of education and awareness to the primary health care providers which would help in improving pregnant women and infant's oral health status along with establishment of dental home.